Pentingnya Perencanaan Dan Pengendalian Piutang Dagang Dalam Meningkatkan Laba Usaha (Studi kasus Pada PT Central Karya Utama di Bandar Lampung) - Defrizal DEFRIZAL; . Ricky; Indrayenti INDRAYENTI (Jurnal Akuntansi dan Keuangan, 2010)
The purpose of this study was to determine the extent to which the company has been carrying out the planning and control of accounts receivable and related to increased corporate profits. Used for data analysis with a qualitative analysis method of comparative analysis or comparison of theory with practice and methods of quantitative analysis by means of the profitability ratio analysis and activity ratios. From the results of research and discussion shows that the rate of turnover of accounts receivable during the period 2004-2008 is always fluctuating, resulting in earnings from year to year, too, is changing.